2023
DOI: 10.1371/journal.pone.0282814
|View full text |Cite
|
Sign up to set email alerts
|

Use of sera cell free DNA (cfDNA) and exovesicle-DNA for the molecular diagnosis of chronic Chagas disease

Noelia Lozano,
Mercedes Gomez Samblas,
Eva Calabuig
et al.

Abstract: Chagas disease, a neglected tropical disease, is now considered a worldwide health concern as a result of migratory movements from Central and South America to other regions that were considered free of the disease, and where the epidemiological risk is limited to transplacental transmission or blood or organ donations from infected persons. Parasite detection in chronically ill patients is restricted to serological tests that only determine infection by previous infection and not the presence of the parasite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…As described elsewhere, it has been shown that DNA-harboring EVs from malaria parasites could stimulate cytosolic pathogen DNA sensors in host monocytes to elicit a cytokine response ( Sisquella et al, 2017 ). On the other hand, cancer related studies of EV-DNA in plasma and other body fluids for new liquid biopsy applications are a reality ( Malkin and Bratman, 2020 ), and this sets a base for understanding and proposing that DNA from pathogens, included in EV fractions, could also be considered a molecular biomarker as it has been proposed in a study with chronic Chagas disease patients, in which the detection of Trypanosoma cruzi nuclear and kinetoplast DNA was performed in serum circulating EVs ( Lozano et al, 2023 ). For the specific case of primary acute meningoencephalitis, a biomarker present in blood instead of cerebrospinal fluid could make the difference in timely and non-invasive diagnosis, and we suggest this could be studied as it has been found that DNA-carrying EVs could cross the intact blood–brain-barrier, being detectable in peripheral blood ( García-Romero et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As described elsewhere, it has been shown that DNA-harboring EVs from malaria parasites could stimulate cytosolic pathogen DNA sensors in host monocytes to elicit a cytokine response ( Sisquella et al, 2017 ). On the other hand, cancer related studies of EV-DNA in plasma and other body fluids for new liquid biopsy applications are a reality ( Malkin and Bratman, 2020 ), and this sets a base for understanding and proposing that DNA from pathogens, included in EV fractions, could also be considered a molecular biomarker as it has been proposed in a study with chronic Chagas disease patients, in which the detection of Trypanosoma cruzi nuclear and kinetoplast DNA was performed in serum circulating EVs ( Lozano et al, 2023 ). For the specific case of primary acute meningoencephalitis, a biomarker present in blood instead of cerebrospinal fluid could make the difference in timely and non-invasive diagnosis, and we suggest this could be studied as it has been found that DNA-carrying EVs could cross the intact blood–brain-barrier, being detectable in peripheral blood ( García-Romero et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%